Cryptic eco‐evolutionary feedback in the city: Urban evolution of prey dampens the effect of urban evolution of the predator. Issue 3 (7th November 2021) - Brans, Kristien I.; Tüzün, Nedim; Sentis, Arnaud; De Meester, Luc; Stoks, Robby
Abstract: Most research on eco‐evolutionary feedbacks focuses on ecological consequences of evolution in a single species. This ignores the fact that evolution in response to a shared environmental factor in multiple species involved in interactions could alter the net cumulative effect of evolution on ecology. We empirically tested whether urbanization‐driven evolution in a predator (nymphs of the damselfly Ischnura elegans ) and its prey (the water flea Daphnia magna ) jointly shape the outcome of predation under simulated heatwaves. Both interactors show genetic trait adaptation to urbanization, particularly to higher temperatures. We cross‐exposed common‐garden reared damselflies and Daphnia from replicated urban and rural populations, and quantified predation rates and functional response traits. Urban damselfly nymphs showed higher encounter and predation rates than rural damselflies when exposed to rural prey, but this difference disappeared when they preyed on urban Daphnia . This represents a case of a cryptic evo‐to‐eco feedback, where the evolution of one species dampens the effects of the evolution of another species on their interaction strength. The effects of evolution of each single species were strong: the scenario in which only the predator or prey was adapted to urbanization resulted in a c . 250% increase in encounter rate and a c . 25% increase in predation rate, compared to the rural predator–rural prey combination. Our results provide unique evidence for eco‐evolutionary feedbacks in cities, and underscore the importance of a multi‐species approach in eco‐evolutionary dynamics research. Abstract : How urbanization shapes species interactions is relatively unknown. The authors show high predation rates of urban damselfly nymphs compared to rural ones when preying on rural, but not urban, Daphnia . This represents a previously undocumented case of a 'cryptic evo‐to‐eco feedback': evolution of one species dampens the effects of evolution of another species on their interaction. (Drawing by Stephen Thackeray, 2018.) Samenvatting: Onderzoek naar eco‐evolutionaire terugkoppelingen focust vaak op de ecologische gevolgen van evolutie in één soort. Bijgevolg negeert men de mogelijkheid dat evolutionaire veranderingen van meerdere interagerende soorten als respons op een gedeelde omgevingsverandering met elkaar kunnen interfereren en zo het netto effect van evolutie op ecologische processen kan veranderen. We testten empirisch of door verstedelijking gedreven evolutie in een predator (larven van de waterjuffer Ischnura elegans ) en zijn prooi (de watervlo Daphnia magna ) de uitkomst van predatie onder gesimuleerde hittegolven beïnvloedt. Beide interactoren vertonen genetische adaptatie aan de stadsomgeving, meer specifiek de daar voorkomende hogere temperaturen. We stelden waterjuffers en watervlooien, afkomstig van gerepliceerde stedelijke en rurale populaties en opgegroeid in een gestandaardiseerde laboratoriumomgeving, bloot aan elkaar volgens een experimenteel design waarbij alle combinaties van herkomst van prooi en predator werden getest. We kwantificeerden telkens de predatiesnelheid en functionele respons‐kenmerken. Stedelijke waterjufferlarven vertoonden een hogere ontmoetings‐ en predatiesnelheid dan larven afkomstig uit rurale gebieden wanneer ze blootgesteld werden aan rurale Daphnia, maar niet wanneer ze blootgesteld werden aan Daphnia afkomstig uit de stad. Deze bevinding wijst op een cryptische evo‐naar‐eco terugkoppeling, waarbij evolutie in één van de soorten het effect van evolutie van de andere soort op de sterkte van hun interactie dempt. De effecten van evolutie in elke soort apart waren sterk: de scenario's waarin enkel de predator of de prooi aangepast was aan de stadsomgeving resulteerde in een c . 250% stijging van de ontmoetingssnelheid en een c . 25% verhoging van de predatiesnelheid, in vergelijking met een situatie waarbij een rurale predator met een rurale prooi was gecombineerd. Deze resultaten leveren uniek bewijs voor een eco‐evolutionaire terugkoppeling in steden en onderlijnen het belang van een multi‐soorten benadering in het onderzoek naar eco‐evolutionaire dynamieken.